Tanggung Jawab Jepang Dalam Scientific Whaling Di Laut Lepas Berdasarkan Perspektif Hukum Lingkungan Internasional - Amin Rais; Maria Maya Lestari; Adi Tiara Putri (Nagari Law Review, 2023)
The Japanese Antarctic Research Program II is a special permit based on the provisions of Article 8 paragraph 1 of the International Convention for the Regulation of Whaling 1946. In 2014 the International Court of Justice issued a ruling that the Japanese Antarctic Research Program II was not included in the provisions of Article 8 paragraph 1 of the International Convention for the Regulation of Whaling 1946, caused the Japanese Antarctic Research Program II to violate international environmental law. The purpose of this study was to determine the existence of the Japanese Antarctic Research Program II based on the perspective of international environmental law and to determine the responsibility of the Japanese state in scientific whaling activities based on the perspective of international environmental law. This type of research is normative legal research using a case approach by conducting a study based on the decision of the International Court of Justice No. 226 of 2014 (Australia v. Japan: New Zealand Intervening). The results of this study, the existence of a special permit for Japanese Antarctic Research Program II is allowed under the provisions of the International Convention for the Regulation of Whaling 1946 and the review of the scientific committee of the International Whaling Commission, but in practice the special permit for this research is not in accordance with the research plan and has many weaknesses so that the Japanese Antarctic Research Program II does not include a special permit for scientific research as contained in Article 8 paragraph 1 of the International Convention of the Regulation of Whaling 1946. Based on the perspective of international environmental law, Japan has subjective responsibility in the form of restitution of the Antarctic Ocean nature reserve for whale conservation and whale sustainability.